Interface Structure‐Dependent Grain Growth Behavior in Polycrystals - Kang, Suk‐Joong L; Jung, Yang‐Il; Jung, Sang‐Hyun; Fisher, John G (Microstructural Design of Advanced Engineering Materials, 2013)
A wide variety of grain growth behaviors takes place in polycrystals, including stationary or normal grain growth, and various types of nonstationary grain growth for example, abnormal grain growth and stagnant grain growth. This chapter describes the behavior and kinetics of grain growth with respect to the interface structure, either rough (atomically disordered) or faceted (atomically ordered). The equilibrium shape of a crystal is first described, followed by the effect of interface structure on interface migration. Various types of grain growth behavior in single as well as two phase (solid–liquid) polycrystalline systems are then explained in terms of the migration behavior of the interface, which is governed by the interface structure. A model of grain growth via mixed control (interface reaction and diffusion) has been introduced and the principle of microstructural evolution developed. The generality of the developed principle of microstructural evolution is supported by various types of grain growth behavior observed in both ceramic and metallic systems.